Is Cocoa Being Valorized? - Graue, Erwin (The Review of Economics and Statistics, 1950)
THIS paper has to do with an analysis of the behavior of the price of cocoa for the purpose of determining whether or not particular influences have gained ascendancy in the control over the cocoa market. Since the termination of price controls by the OPA in October I946, the price of cocoa has advanced from I4.95 cents per pound to more than 50 cents. The New York cocoa market is said to have been submitted to a squeeze by the British West African Produce Control Boards; ' and His Majesty's Government has gone on record to ensure that the Boards' operations are brought into conformity with any international obligations which it may have assumed, or may in the future assume.2 There are conflicting reports between what appears to be the avowed attitude of the British Government in establishing central marketing agencies, and the statement by The Econzomist that this latest rise in cocoa prices . . . is coincidence, and not design, which has produced the new marketing organizations and a steep rise in world cocoa prices at the same point of time.' For the American economy the spectacular rise in the price of cocoa is of twofold importance: (X) because the yearly imports of cocoa by the United States are about 40 per cent of the total world output of which, in recent years, more than one-half has originated in British West Africa;4 and (2) because it is said that the advance in price is a result of short-time reduced output, and, possibly, in the long run, a question of monopoly that is fundamental to the whole control scheme.5